1418. The Relationship Between Modifiable Health Behaviors and Health Literacy in People with HIV is Complicated by Multiple Factors. (15th December 2022) - Richey, Lauren; Schroeder, Jonathan; Apolzan, John; Mistretta, Kyle; Holloway, Kaila; Lin, Hui-Yi; Arnold, Connie; Welsh, David
Abstract: Background: People with HIV (PWH) who achieve viral suppression have a normal lifespan, however, they now contend with more cardio-metabolic disease and exaggerated rates of malignancies. The etiology of these disparate rates of comorbidities are multifactorial but likely include modifiable behaviors such as smoking, poor diet, and substance use. We created a multidisciplinary team to study health behaviors in PWH. The team included researchers and HIV clinics in three Louisiana cities; New Orleans, Baton Rouge, and Shreveport, forming the Louisiana Translational Collaborative on Health Behaviors [LATCH] network. We hypothesized that patients with low health literacy would have higher BMIs and higher usage of tobacco and illicit drugs. Methods: PWH aged ≥ 18 were recruited from three HIV clinics during regular appointments. Participants completed surveys using standardized tools that assessed diet, physical activity, health literacy, tobacco and substance use. Weight and height were also recorded. Results: 100 PWH were enrolled. Most were African American (80%), men (57%), and the mean age was 50.72 (range 21-70). Mean BMI was 30.2 (range 18-51). Limited health literacy was found in 50% (REALM-SF < 7). Past month drug use was reported in 24%. Lifetime tobacco use was reported in 59%, with 31% reporting current use. For BMI, the average BMI for those with low health literacy (REALM-SF < 7) was 29.26 compared to 30.62 for those with adequate health literacy (REALM-SF 7) (p< .001). Among patients with limited literacy (REALM-SF < 7) 27.1% reported current tobacco use, compared with 36.7% of those with adequate literacy (REALM-SF 7) (p=0.68). Among patients with limited literacy (REALM-SF < 7) 25% reported past month drug use, compared with 24.5% of those with adequate literacy (REALM-SF 7) (p=0.59). Conclusion: We hypothesized that PWH with lower health literacy would have higher BMIs, which was the opposite of what we found. We also found higher rates of smoking among those with higher health literacy although it was not significant. No differences were seen in past month drug use. Health literacy and education to improve health literacy may not directly impact modifiable health behaviors which are likely influenced by many different factors. Disclosures: All Authors : No reported disclosures.